1995
DOI: 10.1039/an9952002879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ractopamine cross-reactivity in several commercially available β-agonist enzyme immunoassay kits

Abstract: Several enzyme immunoassay test kits are commercially available for screening of matrices including cattle feed, tissues, faeces and urine for the presence of beta-agonists. The kits utilized for this evaluation offer sensitivity as low as 0.1 ng ml-1 (assay solution concentration, not test sample). Evaluation of ractopamine hydrochloride (LY31537) solutions at concentrations as high as 1000 ng ml-1, using six different kits from four different manufacturers, showed cross-reactivity of less than 0.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The concentrations of RCT given to the experimental animals (0.1 mg kg 21 d 21 ) were in the region of dose required to cause growth promotion. 8,11 The concentrations of RCT residues detected as a result of this treatment were substantial, at least during the medication phase. There was considerable animal to animal variation in the residue levels measured during this phase and surprisingly the concentrations of RCT present in the urine samples appeared to decline during the first week of treatment despite a steady intake of drug by the animals.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of RCT given to the experimental animals (0.1 mg kg 21 d 21 ) were in the region of dose required to cause growth promotion. 8,11 The concentrations of RCT residues detected as a result of this treatment were substantial, at least during the medication phase. There was considerable animal to animal variation in the residue levels measured during this phase and surprisingly the concentrations of RCT present in the urine samples appeared to decline during the first week of treatment despite a steady intake of drug by the animals.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the two methods was moderate, at r 2 ) 0.73. A report using commercially available β-adrenergic agonist immunoassay kits demonstrated no crossreactivity with ractopamine (15) indicating that they would not be useful for ractopamine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…All these compounds showed no cross-reactivity with the RAC antibody except for dobutamine. Wicker et al [18] reported that if the antibody is developed against a compound with a very similar structure, crossreactivity will likely occur. In conclusion, it was reasonable that dobutamine which has a very similar structure to RAC showed 7.5% crossreactivity with RAC.…”
Section: Resultsmentioning
confidence: 99%